World War II and Wits student politics - Murray, Bruce (My University, 1993)
Both nationally and on the Wits campus, the war years constituted a major divide in the realm of student politics. On the national level, the war promoted three developments. Firstly, for the duration of the war, there was virtually a complete breakdown in relations between the English-medium and predominantly Afrikaans-medium university institutions, bringing to a halt the traditional intervarsity competitions. The breakdown was effected at the instigation of the highly politicised Afrikaanse Nasionale Studentebond (ANS), the national organisation formed by the Afrikaner SRCs in the 1930s. Secondly, the war turned into a graveyard for the ANS, which identified itself with the paramilitary, pro-Nazi Ossewabrandwag (OB). The history of the ANS has yet to be written, but it is evident that the organisation fragmented badly in 1942 in the face of the drive of the parliamentary National Party to assert its ascendancy over political Afrikanerdom. After 1942 teacher training colleges, rather than university institutions, provided the ANS with its chief support base. In 1948, following the formation of the Nationalist Government, the ANS was replaced by the Afrikaanse Studentebond (ASB). Thirdly, the outcome of the war was crucial in determining the character of the National Union of South African Students (NUSAS), effectively the national organisation of English-speaking students. During the war NUSAS sought to keep itself intact by averting polarising issues, notably the admission to its ranks of Fort Hare Native College. The outcome of the war, perceived as a defeat for the forces of Fascism and racism, ultimately ensured the admission of Fort Hare, and NUSAS finally emerged as a 'progressive' organisation. On the Wits campus, student organisation and political culture underwent some profound changes as a consequence of the war, and the issues it raised. For the first time students at Wits acquired a real sense of being part of the politics of the country; an organised left appeared on campus in the form of the Federation of Progressive Students (FOPS)…
African Studies Seminar series. Paper presented 11 October 1993
Keywords: University of the Witwatersrand. History; Students. South Africa. Political activity. History